University Spaces as Agents of National Belonging: Analysing the Visual Culture of Public Universities' Campuses in India and Pakistan - Laraib Niaz; Kusha Anand (MDPI AG, 2021)
This article discusses the role of 'space' in Indian and Pakistani public sector universities in fostering national pride. University spaces have been highlighted, in both countries, for being used by the governments as agents fostering the national narrative yet there is limited research on how these spaces contribute to the visual culture of educational institutions and in the inculcation of nationalistic values. This article adds to the conversations regarding the fostering of national belonging and pride in universities by exploring space as a constitutive element of the visual culture of the higher education environment in India and Pakistan. In both countries, the physical spaces of public universities have become platforms for channelling student voices. This research uses two state-funded universities, from Delhi (in India) and Lahore (in Pakistan), and Lefebvre's conception of space to conduct a discourse analysis of bulletin boards, graffiti, statues, sculptures, and any other imagery found online pertaining to the campuses and analyse how it is a 'conceived' and 'perceived' aspect of the visual culture of the universities. It adds to current scholarly conversations on national pride and consciousness in India and Pakistan by showing how university spaces can potentially play an active role in promoting the state's narrative in students' or educators' everyday educational experiences.